RAPD Analysis, Synthesis of Zinc Oxide Nanoparticles Derived from Aerva lanata Flower, Characterization and Antimicrobial Screening - GANESAN, THAMARAISELVI; MUTHUKRISHNAN, SURIYAVATHANA MUTHUKRISHNAN; † BRAIVY ANTO, † BRAIVY ANTO; MANIKANDAN MATHAIYAN, MANIKANDAN MATHAIYAN; SOBIYA PRADEEP KUMAR, SOBIYA PRADEEP KUMAR; R. JAYAPRAAKASH, R. JAYAPRAAKASH; M.SUGANYA, M.SUGANYA (Asian Journal of Chemistry, 2023)
Nanoparticles and plant phytochemicals are receiving great interest between materials and drug discovery research. Hence, this research work synthesised the zinc oxide nanoparticle (ZnONP) using Pashanabheda (Aerva lanata), which is employed as an antiurolithiatic in Ayurveda. The Amaranthaceae member Aerva lanata flower was selected as the source due to the diversity of genetic alterations which displays in response to different environmental and geographical conditions. A.lanata flower aqueous extract was used to synthesis zinc oxide nanoparticles, which were then characterised by UV, FTIR, XRD, and scanning electron microscopy. Due to flower’s chemical make-up and abundance of functional groups, the derived ZnO nanoparticles were found to be effective at bio-reduction and capping. Antibacterial assay against B. subtilis, S. aureus, K. pneumonia and Pseudomonous using ZnONp of A. lanata flower exhibited excellent inhibition zones between 11 mm and 18 mm for 100 μg/ml. concentration.